Planning for a different kind of sea change: lessons from Australia for sea level rise and coastal flooding. (7th February 2021) - Dedekorkut-Howes, Ayşın; Torabi, Elnaz; Howes, Michael
ABSTRACT: Climate change increases hazards for coastal cities where a large proportion of the world's population lives. Adaptation to its impacts ought to be a key focus for planning and policymaking in highly vulnerable countries like Australia. This responsibility, however, has been largely left to local councils with mixed results. This leaves substantial parts of the population at risk where adaptation plans are lacking. Even worse, since the impacts of climate change do not respect jurisdictional boundaries, there is a spill-over risk where good adaptation planning by one council may be undermined by the lack of action in an adjacent council. These risks can be reduced if state and federal governments provide more consistent support and guidance. This paper takes an integrated approach in comparing the relevant legislation, policies, plans, and strategies related to coastal management across the national and state/territory jurisdictions in Australia. The findings indicate that there are major differences, with some states (South Australia, Victoria, Western Australia, and Queensland) having more detailed policies and plans for addressing sea level rise and coastal flooding. The findings have implications beyond Australia, particularly for those countries with more devolved or federal systems of government, and provide key lessons for adaptation to climate change. Key policy insights In the absence of national guidance and leadership, climate adaptation responses will remain uneven across jurisdictions placing more of the population at risk and undermining what adaptation plans there are. National, state, and territory policies or plans are more effective if they are consistent over time, but they are undermined by reversals when governments change between political parties that have widely varying views on climate change. Effective long-term adaptation policymaking and planning therefore require a bipartisan commitment and consistent political will across the major political parties to prioritize the problem and commit significant public resources to a response.